Objective Imputation in Peruvian Case Law - Villavicencio Terreros, Felipe (2007)
The present work makes an approach to the evolution of the criteria of criminal imputation in the Peruvian legal system. According to the author, Peruvian criminal law has undergone an interesting transformation in terms of criminal imputation criteria. Under this premise, the article analyzes the doctrinal and case law positions regarding objective imputation, starting with causality as the basis of such imputation. In this way, the author addresses the elements of objective imputation, such as permissible risk, the principle of trust, the prohibition of return, objective imputation in participation and complicity, imputation to the victim, the risk relationship, deviant causal nexus, interruption of the causal nexus, among others.